Prospective Evaluation of the Pathologic Diagnosis and Treatment Outcomes of Pediatric Burkitt Lymphoma in the Central American Pediatric Hematology-Oncology Association Consortium - Priya Kumar; Monika L. Metzger; John K. Choi; Godwin Job; Teresa C. Santiago; Armando Peña; Miguela A. Caniza; Asya Agulnik; Pascale Y. Gassant; Wendy C. Gómez García; Patricia J. Calderón; Claudia Garrido; et al. (JCO Global Oncology)
PURPOSEClinical and histopathologic diagnosis of pediatric mature B-cell lymphomas (eg, Burkitt lymphoma [BL]) must be accurate to select appropriate risk-based treatment. The Central American Pediatric Hematology-Oncology Association (AHOPCA) in 2000 implemented standardized, resource-adapted treatments for these lymphomas. We evaluated the concordance of local histopathologic diagnoses through central review, determined the impact on therapy selection, and described the clinical characteristics and outcomes of pediatric patients with these lymphomas. We suggest recommendations to improve the accuracy of diagnoses.METHODSPathology samples and reports were submitted by six AHOPCA sites to St Jude Children's Research Hospital for central review. The concordance of sample assessments was evaluated using three criteria: histologic diagnosis, morphology, and immunohistochemistry. Clinical characteristics, treatment, and outcomes were also analyzed.RESULTSOf the 68 eligible patients, 53 (78%) received an accurate pathologic diagnosis of BL. For nine (13%) patients, diagnoses changes with therapy implications were made upon central review, while in six patients, there was a minor disagreement with no therapy implications. Most (87%) patients presented with advanced disease. Detailed cellular features were absent in many reports, and immunohistochemistry was routinely performed at only one site. Of the 50 patients whose treatment data were reported, 44 (88%) completed therapy, five died during treatment, and one abandoned treatment. Treatment outcome was satisfactory: 3-year event-free survival was 74% (SE ± 11%), and overall survival was 73% (SE ± 11%).CONCLUSIONPathology laboratories in limited-resource hospitals and regions need further optimization to increase accurate diagnoses of mature B-cell lymphomas. Creating regional pathology networks will enhance diagnostic support. Despite resource limitations and advanced disease at presentation, the AHOPCA sites' adapted treatment strategies have improved patient outcomes.